Who Are Our People? Toward a Christian Witness against Borders. (8th March 2018) - Ashworth, Justin P.
Abstract: Christian arguments for state borders are grounded in the preferential option for one's people, that is, the conviction that the needs of co‐citizens must be given priority over those of foreigners. Theologians often find support for this conviction in the doctrines of human finitude and divine providence: limited resources make it impossible to love all people equally, so we must choose where to start; since God has providentially placed near‐neighbors (citizens) in our paths, we honor God's design by keeping in mind their proximate needs in our moral deliberations. I argue that there are several flaws in such defenses of borders. First, they overlook the violence inherent in actually‐existing border practices; second, they misidentify fellow citizens as our people, thereby underwriting the church's captivity to state violence. I argue that a sounder theological view of borders requires Christians to adopt a preferential option for God's people. The church catholic is a borderless people committed to bodily solidarity and sharing with the vulnerable. Inasmuch as the church is a people already gathered in anticipation of the final joining of all things in Jesus Christ, ecclesial borderlessness serves as the horizon for all peoples.